PENGARUH CITRA MEREK, KUALITAS PRODUK DAN E-WOM TERHADAP KEPUTUSAN PEMBELIAN SKINCARE MS GLOW PADA E-COMMERCE TOKOPEDIA DI KOTA BATAM - Yolanda, Tika; Purba, Tiurniari (LPPM Universitas Putera Batam, 2025)
This research aims to examine the influence of brand image, product quality and e-WOM on purchasing decisions for MS Glow Skincare on Tokopedia e-Commerce in Batam City. This study uses a quantitative research method. The research sample consisted of 96 respondents who were people who had purchased and used MS Glow Skincare on Tokopedia e-Commerce in the Sagulung District, Batam City. The data collection method used was primary data. Data processing used the SPSS Version 26 program. Based on the data and analysis that have been carried out, this study shows that brand image positively and significantly influences purchasing decisions for MS Glow Skincare on Tokopedia e-Commerce in Batam City. In addition, product quality positively and significantly influences purchasing decisions for MS Glow Skincare on Tokopedia e-Commerce in Batam City. In e-WOM, it positively and significantly influences purchasing decisions for MS Glow Skincare on Tokopedia e-Commerce in Batam City. And simultaneously, brand image, product quality and e-WOM positively and significantly influence purchasing decisions for MS Glow Skincare on Tokopedia e-Commerce in Batam City